2019
DOI: 10.1080/16078454.2019.1591570
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic splenectomy for splenic lymphomas: analysis of the National Cancer Data Base

Abstract: Objectives: To examine the use of splenectomy, chemotherapy, and subsequent overall survival (OS) in contemporary patients with splenic lymphomas. Methods: We analyzed records of 6450 patients with various splenic lymphomas recorded in the National Cancer Data Base (2004-2013). Survival was compared using Mantel-Byer test to account for guarantee-time bias, stratified by age, sex, comorbidities, and lymphoma stage. Results: Splenectomy rate was overall 58%, and varied from 49% in splenic marginal zone (SMZL) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
0
18
2
Order By: Relevance
“…When diagnosed, malignant splenic tumors do not always require splenectomy. Accumulating evidence has shown that splenic lymphoma can be effectively treated with immunochemotherapy, resulting in a decreasing need for therapeutic splenectomy[ 19 , 20 ]. Splenectomy for splenic lymphoma is reserved for patients who experience abdominal fullness due to large spleens and cytopenia due to spleen sequestration[ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When diagnosed, malignant splenic tumors do not always require splenectomy. Accumulating evidence has shown that splenic lymphoma can be effectively treated with immunochemotherapy, resulting in a decreasing need for therapeutic splenectomy[ 19 , 20 ]. Splenectomy for splenic lymphoma is reserved for patients who experience abdominal fullness due to large spleens and cytopenia due to spleen sequestration[ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that splenic lymphoma can be effectively treated with immunochemotherapy, resulting in a decreasing need for therapeutic splenectomy[ 19 , 20 ]. Splenectomy for splenic lymphoma is reserved for patients who experience abdominal fullness due to large spleens and cytopenia due to spleen sequestration[ 19 , 20 ]. Diagnosis of tissue proof to determine the nature of lymphoma could be another important indication of splenectomy for highly suspected systemic lymphoma with absence of a definite diagnosis from another site.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, splenectomy has been shown to be relatively safe. A 2019 review by Fallah and Olszewski of 6450 patients with splenic lymphoma in the National Cancer Data Base from 2004 to 2013 found that 58% of patients were treated with splenectomy, with a thirty-day overall mortality of 4% [2].…”
Section: Discussionmentioning
confidence: 99%
“…While mantle cell lymphoma and plasma cell leukaemia do not typically require splenectomy for management, 7,8 there may be diagnostic and therapeutic benefits. Non‐nodal mantle cell lymphoma may have a long remission post splenectomy 9 and rituximab therapy has been linked with increased risk of PSSR 10 . The downside is that splenectomy may delay time to chemotherapy in patients with aggressive disease such as plasma cell leukaemia which benefits from early chemotherapy 9 …”
Section: Figurementioning
confidence: 99%
“…Non‐nodal mantle cell lymphoma may have a long remission post splenectomy 9 and rituximab therapy has been linked with increased risk of PSSR 10 . The downside is that splenectomy may delay time to chemotherapy in patients with aggressive disease such as plasma cell leukaemia which benefits from early chemotherapy 9 …”
Section: Figurementioning
confidence: 99%